Answer:
38.5
Step-by-step explanation:
Lets say, first number = x
Second number = 3x+7
Total = 49
(x)+(3x+7)= 49
4x+7 = 49
4x = 42
x = 42/4
x= 10.5
x= 10.5
3x+7 = 3(10.5)+7 = 38.5
Hope this helps!!
The answer to the question
This is impossible to answer without knowing what the sets A and B contain (and what ξ even refers to - universal set?).
However, we have
(A U B)' = A' ∩ B'
so that
(A ∩ B) U (A U B)' = (A ∩ B) U (A' ∩ B') = (A U A') ∩ (B U B')
If ξ is indeed the universal set, then both A U A' = ξ and B U B' = ξ, so we end up with ξ ∩ ξ = ξ.
Answer:
-1
Step-by-step explanation:
Answer:
10/16
Step-by-step explanation:
Just multiply the denominator and the numerator by 2 and wha la you get 10/16 hope it helps!